Dimensions of School Food Environments and Their Association with Anthropometric and Dietary Outcomes in Children: The Healthy Communities Study. (29th May 2020) - Tsai, Marisa; Frongillo, Edward; Ritchie, Lorrene; Woodward-Lopez, Gail; Au, Lauren
Abstract: Objectives: While it has been recommended that schools be the hub of efforts to improve child nutrition, research describing dimensions of U.S. school nutrition environments is limited. This study used exploratory factor analysis to estimate dimensions of school nutrition environments and examined their association with child anthropometric and dietary measures. Methods: Cross-sectional analyses of 386 U.S. elementary and middle schools and 4635 children from the national Healthy Communities Study (2013–2015) was conducted. Three complementary instruments to assess the school nutrition environment were used to create 34 variables. Data were collected by observation and surveys. Factor analysis was done with orthogonal rotation. Mixed-effects regression models examined the multivariate-adjusted associations of dimensions of school nutrition environments with child anthropometric and dietary measures accounting for community and school variation. Results: Six dimensions of school nutrition environments were derived: 1) nutrition education; 2) fruit and vegetable availability; 3) dining environment, including size and crowding; 4) school meal quality, including compliance with competitive food standards, amount of whole grains, and high fat foods; 5) school participation in state and federal nutrition programs; and 6) self-reported implementation of school wellness policies. Higher school meal quality was associated with lower added sugars intake (ß = –0.94, P  < 0.01), better dining environment was associated with higher body mass index z scores (ß = 0.04, P  = 0.03), and higher implementation of school wellness policies was associated with higher waist circumference (ß = 0.54, P  < 0.01). Conclusions: Schools serving meals of higher nutritional quality had children with lower added sugars intake. Associations between dining environment and BMI-z; and implementation of school wellness policies and waist circumference were counterintuitive and may be due to school selection or the inability of cross-sectional data to capture relationships with longer-term health outcomes. More efforts are needed to identify school nutrition environments that have the greatest impact on child diet and adiposity outcomes. Funding Sources: National Heart, Lung, and Blood Institute #K01HL131630.